DEVELOPMENT AND EVALUATION OF NOVEL DIABETES NUTRITION EDUCATION TOOLKIT TAILORED FOR MIZO ADULTS - MALSAWMKIMI HAUHNAR (The Journal of Research ANGRAU, 2024)
The study aimed to develop and evaluate a Diabetes Nutrition Education Toolkit tailored for Mizo adults to be used interactively between patients and dietitians. The Diabetes Nutrition Education Toolkit was developed between September 2022 and February 2023. It consisted of seven interactive nutrition education modules that provided practical tools to improve diet adherence. The appropriateness of the toolkit was evaluated by the “Suitability of Assessment of Materials (SAM)” by two independent raters. The readability grade level was assessed by the average readability score of seven online tools, with each module rated “superior. The SAM score for each module was rated “superior” (93.5–100%) having a mean score of 97.46%. Cohen’s kappa statistically tested inter-rater reliability, and the strength of agreement varied between “substantial” and “almost perfect.” The Diabetes Nutrition Education Toolkit is suitable for the intended population and can be used as digital or printed material to supplement diabetes nutrition therapy.